Proceso de comunicación de los programas del MIES para adultos mayores modalidad virtual Parroquia La Unión - Arias Moran, Ginger Yaritza (2021)
The Ministry of Economic and Social Inclusion (MIES) aims to care for and protect adults, this with the aim of establishing whether the communication strategies used by this institution were able to satisfy and achieve their function during the COVID-19 pandemic. For this reason, the MIES considered giving the courses or workshops through teleworking, relying on social networks as indispensable tools. It will also serve to determine if the method they used was viable or feasible for long-lived people. The MIES is a corporation that aims to prioritize the most vulnerable population in the state to guarantee a better quality of life, both socially and economically, for this reason it is essential to know the meaning of the acronym MIES and in the same way to know what the function it fulfills in the country. The care centers are guided by the political lines to improve the quality of life of the elderly. Currently, the internet, being the channel that predominates in the method of obtaining information, becomes accessible to the educational system, thus facilitating the development of lucrative activities.